Novel NEK8 Mutations Cause Severe Syndromic Renal Cystic Dysplasia through YAP Dysregulation. - Valentina Grampa; Marion Delous; Mohamad Zaidan; Gweltas Odye; Sophie Thomas; Nadia Elkhartoufi; Emilie Filhol; Olivier Niel; Flora Silbermann; Corinne Lebreton; Sophie Collardeau-Frachon; Isabelle Rouvet; et al. (PLoS Genetics)
Ciliopathies are a group of genetic multi-systemic disorders related to dysfunction of the primary cilium, a sensory organelle present at the cell surface that regulates key signaling pathways during development and tissue homeostasis. In order to identify novel genes whose mutations would cause severe developmental ciliopathies, >500 patients/fetuses were analyzed by a targeted high throughput sequencing approach allowing exome sequencing of >1200 ciliary genes. NEK8/NPHP9 mutations were identified in five cases with severe overlapping phenotypes including renal cystic dysplasia/hypodysplasia, situs inversus, cardiopathy with hypertrophic septum and bile duct paucity. These cases highlight a genotype-phenotype correlation, with missense and nonsense mutations associated with hypodysplasia and enlarged cystic organs, respectively. Functional analyses of NEK8 mutations in patient fibroblasts and mIMCD3 cells showed that these mutations differentially affect ciliogenesis, proliferation/apoptosis/DNA damage response, as well as epithelial morphogenesis. Notably, missense mutations exacerbated some of the defects due to NEK8 loss of function, highlighting their likely gain-of-function effect. We also showed that NEK8 missense and loss-of-function mutations differentially affect the regulation of the main Hippo signaling effector, YAP, as well as the expression of its target genes in patient fibroblasts and renal cells. YAP imbalance was also observed in enlarged spheroids of Nek8-invalidated renal epithelial cells grown in 3D culture, as well as in cystic kidneys of Jck mice. Moreover, co-injection of nek8 MO with WT or mutated NEK8-GFP RNA in zebrafish embryos led to shortened dorsally curved body axis, similar to embryos injected with human YAP RNA. Finally, treatment with Verteporfin, an inhibitor of YAP transcriptional activity, partially rescued the 3D spheroid defects of Nek8-invalidated cells and the abnormalities of NEK8-overexpressing zebrafish embryos. Altogether, our study demonstrates that NEK8 human mutations cause major organ developmental defects due to altered ciliogenesis and cell differentiation/proliferation through deregulation of the Hippo pathway.